Prototype Design Remote Smart Car 4WD Robot Car with Additional Power Photovoltaic Source Integrated Arduino - Aldhi, Muhammad; Satria, Habib; Mungkin, Moranain; Dayana, Indri; Salam, Rudi (Jurnal Internasional Teknik, Teknologi dan Ilmu Pengetahuan Alam, 2024)
The problem addressed in this research is designing an Electric Car Prototype, a technology design using Arduino Uno, L298N Driver Module, and HC-06 Bluetooth sensor which is controlled automatically using an application. The method used is a hybrid PLTS (Solar Power Plant) system based on Arduino Uno. This prototype combines electrical energy from batteries with solar energy produced by solar panels, and the main controller is Arduino Uno. Tests were carried out to evaluate the performance and efficiency of this electric car. The results of solar panel experiments in designing electric car prototypes, testing will be carried out on the efficiency of solar panels on the power produced. The following is the data from the experimental results measured through the following table 2 experiments. solar panels were installed on the roof or other parts exposed to sunlight on a prototype electric car. Solar panels consist of photovoltaic solar cells which are capable of converting solar energy into electrical energy. When sunlight falls on a solar panel, the solar cell produces an electric current. The electric current generated from the solar cell is then channeled to the charging module to charge the battery. The battery charging module regulates the voltage and electric current according to battery charging needs. This is important so that the battery does not receive too much or too little power during the charging process. After passing through the battery charging module, the electrical energy from the solar panels is used to charge the electric car battery. Electric car batteries function as energy storage which is used to control the engine and other electronic systems in the car. Obtained were the development of an environmentally friendly and sustainable electric vehicle.